Graph Data Processing with Cypher : A Practical Guide to Building Graph Traversal Queries Using the Cypher Syntax on Neo4j - Anthapu, Ravindranatha (Packt Publishing, Limited, 2022)
Get acquainted with Cypher in a guided manner quickly and learn how to query the graph databases with efficient and performant queries Key Features Work with Cypher syntax and semantics while building graph traversal queries Get up and running with advanced Cypher concepts like List, Maps, OPTIONAL MATCH Master best practices in writing effective queries leveraging data modeling and patterns Book Description While it is easy to learn and understand the Cypher declarative language for querying graph databases, it can be very difficult to master it. As graph databases are becoming more mainstream, there is a dearth of content and guidance for developers to leverage database capabilities fully. This book fills the information gap by describing graph traversal patterns in a simple and readable way. This book provides a guided tour of Cypher from understanding the syntax, building a graph data model, and loading the data into graphs to building queries and profiling the queries for best performance. It introduces APOC utilities that can augment Cypher queries to build complex queries. You'll also be introduced to visualization tools such as Bloom to get the most out of the graph when presenting the results to the end users. After having worked through this book, you'll have become a seasoned Cypher query developer with a good understanding of the query language and how to use it for the best performance. What you will learn Write Cypher queries from basic to advanced level Map the source data to the graph data model in an iterative fashion Load the data into a graph using LOAD CSV, APOC, and client drivers Map the business questions to graph queries effectively Identify query performance issues and fix them Extend capabilities of Cypher using APOC utilities Work with graph visualization tools like Bloom and Browser Who this book is for This book is targeted at Database Administrator, Database Developers, Graph Database Developers, and Graph Database Architects. This book will also help someone migrate from a DBA role to a graph data engineer or data scientist If you are working with graph databases and need to learn Cypher, or are a basic Cypher developer who wants to get better at data modeling and tuning queries to build performant Cypher queries, then this is the book for you.